Implementing inductive grammar instruction with college students taking online English classes - Vez López, Enrique; Abad Pérez, Lucero (Universidad Pedagógica y Tecnológica de Colombia, 2024)
This action research project aimed to investigate the outcomes of implementing an inductive approach to teaching grammar at a public institution in the north of Veracruz, Mexico. This mixed methodology involved 16 students enrolled in online English classes The data were collected by means of diagnostic and achievement tests, semi-structured interviews with students, and observations by colleagues. The results revealed that the students were accustomed to receiving deductive instruction and acting passively in the classroom; thus, more attention needed to be paid to their performance. Additionally, it was discovered that the teacher's role needed to change to one that involved less talking time and more encouragement for students to develop their problem-solving abilities. The results suggest that using an inductive approach to teaching grammar may improve students' language skills and ability to apply their knowledge of grammar to more realistic situations.